Analisis Pengaruh Kemudahan dan Kemanfaatan Terhadap Minat dan Perilaku Menggunakan QRIS Sebagai Alat Pembayaran Pada Usaha Kuliner di Kota Mataram - Sari, Baiq Nirmala; Chaidir, Taufiq; Yudha, I Dewa Ketut (Universitas Mataram, 2024)
The rapid development of digital technology has encouraged Bank Indonesia to set QRIS as the standard payment system in Indonesia. Many micro-entrepreneurs have started using this payment system. They are able to compete and follow the trend of technological developments. The purpose of this study was to analyze the effect of convenience and usefulness on the interest and behavior of using QRIS as a payment method in culinary businesses in Mataram City, the data collection method used a survey sample, the number of respondent samples was 91 micro-entrepreneurs in the culinary sector in Mataram City. The analysis tool used was a mediation regression model with path analysis that adopted the Technology Acceptance Model (TAM) model. The results of the study showed that partially convenience did not have a significant effect, while usefulness had a significant effect on interest in using QRIS, convenience did not affect behavior, conversely usefulness had a significant effect on behavior of use. Convenience on behavior of use mediated by interest did not have a significant effect, while usefulness on behavior of use mediated by interest had a significant effect